2021
DOI: 10.3389/fonc.2021.687730
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Foundation Medicine Testing on Cancer Patients: A Single Academic Centre Experience

Abstract: BackgroundThe use of Next-Generation Sequencing (NGS) has recently allowed significant improvements in cancer treatment. Foundation Medicine® (FM) provides a genomic profiling test based on NGS for a variety of cancers. However, it is unclear if the Foundation Medicine test would result in a better outcome than the standard on-site molecular testing. In this retrospective chart review, we identified the FM cases from an academic Canadian hospital and determined whether these test results improved treatment opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 22 publications
3
8
0
Order By: Relevance
“…The most commonly altered genes by genetic variation of class 4-5 and VUS in this study were consistent with those published in the literature, with TP53 as the most common gene, followed by RAS, PIK3CA, and CDKN2A/B (15,16,19,20). In the present Cancers for which more than five patients had available sequencing results were analyzed.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The most commonly altered genes by genetic variation of class 4-5 and VUS in this study were consistent with those published in the literature, with TP53 as the most common gene, followed by RAS, PIK3CA, and CDKN2A/B (15,16,19,20). In the present Cancers for which more than five patients had available sequencing results were analyzed.…”
Section: Discussionsupporting
confidence: 90%
“…The success rate was 78% for liquid biopsy samples and 88% for FFPE samples (40% of biopsies), indicating that the ability to detect alterations is lower for liquid biopsies. These data are consistent with the literature comparing liquid and tissue biopsy samples (14)(15)(16)(17)(18). Takeda et al showed that the success rate of the NGS assay performed with FFPE samples, including 34% of biopsy specimens, was 96.7% in different types of cancer (19).…”
Section: Discussionsupporting
confidence: 90%
“…Although comprehensive genomic profiling using cancer gene panels has demonstrated value in broadening the treatment options for the patients based on matching a patient’s genomic lesions to cancer driver gene aberrations associated with FDA-approved treatment indications 8,9 , the presence/absence of mutations in such genes does not necessarily translate into improved predictive power for estimating the patient’s response to the potential treatments. While for some drugs, the variation in drug response can be explained by a very specific mutation, for instance, BRAF V600E mutation is a strong predictor for response to Vemurafenib in metastatic melanoma 4 , for many drugs, the knowledge of the mechanism of action is missing.…”
Section: Mainmentioning
confidence: 99%
“…41 Another study using a different CGP test (FoundationOne), which has both liquid biopsy-and tissue biopsy-based assays, reported a cost of $4,700 per sample in 2021. 42 In the US, certain commercially available CGP tests require blood samples to be sent to central laboratories for analysis, and the results are reported to the donor's health care provider. One of these tests (Guardant360) costs US$5,000 for people paying out-of-pocket.…”
Section: Costmentioning
confidence: 99%